2019
DOI: 10.3389/fneur.2019.00918
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Disability Due to Japanese Encephalitis in Elderly Adults: Evidence From an Adult Tertiary Care Center in West China

Abstract: Japanese encephalitis (JE) is the most important cause of viral encephalitis in Asia, with most cases seen in children <15 years. Recently, cases of JE in people aged >50 years have been increasingly reported, but the clinical presentation in these cases is largely unknown. We report here the first case series of elderly JE patients from an adult tertiary hospital in West China. Medical records of laboratory-confirmed JE patients diagnosed from January 2011 to September 2018 were reviewed retrospectively. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…However, most adults in China are not vaccinated against the disease, and the incidence of adult morbidity is still relatively high through the transmission of the viruscarrying. One study showed that the number of patients over the age of 15 with JE has been increasing in the past few years, accounting for 82.48% of the total number of patients in 2016, and the proportion of middle-aged and elderly people suffering from JE is also increasing, rising from 2.93% in 2011 to 21.82% in 2016 [5]. However, geriatric patients are not given enough attention because this age group is not listed as an at-risk population [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, most adults in China are not vaccinated against the disease, and the incidence of adult morbidity is still relatively high through the transmission of the viruscarrying. One study showed that the number of patients over the age of 15 with JE has been increasing in the past few years, accounting for 82.48% of the total number of patients in 2016, and the proportion of middle-aged and elderly people suffering from JE is also increasing, rising from 2.93% in 2011 to 21.82% in 2016 [5]. However, geriatric patients are not given enough attention because this age group is not listed as an at-risk population [6].…”
Section: Discussionmentioning
confidence: 99%
“…Japanese encephalitis (JE) is the most common cause of encephalitis in Asia, affecting mainly children. Adult cases are increasingly reported [ 66 ]. JE is also a relevant cause of encephalitis in the western pacific, and JE cases have also been reported in Australia [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Around 45–64% of survivors show neurological sequelae on hospital discharge [ 72 74 ]. In a Chinese retrospective series of 50 JE patients [ 66 ], 12% died during hospital admission, 75% had significant functional limitations upon discharge, and 39% of survivors had major limitations after 18 months.…”
Section: Methodsmentioning
confidence: 99%
“…However, the age distribution shifted toward adults currently in countries where JE immunization program exists. 7,[9][10][11][12] Due to the introduction of JE vaccine, urbanization and improved sanitary and public health measures, the incidence of JE decreased year by year in many endemic countries. The estimated incidence of JE in Korea was 0.1-1.8 per 1,00,000 population during 1980-1984 and decreased to 0.013-0.055 per 1,00,000 population during 2007-2010.…”
Section: Epidemiologymentioning
confidence: 99%
“… 4 , 6 Several reports show that JE in young children and the elderly were more likely to be associated with severe sequelae and a higher mortality rate than young adults. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%